Optimized computed tomography protocol in pediatric Hodgkin’s lymphoma - K. A. Khasanova; I. E. Tyurin (Инновационная медицина Кубани)
Background. Children with HL are forced to undergo repetitive studies accompanied by radiation, which increases radiation doses. High radiation during studies in children is a huge problem, since the risk of developing complications for patients of this age is much higher than for adults.Purpose. To optimize the computed tomography protocol in pediatric Hodgkin's lymphoma for radiation dose reduction by reducing the scanning phases.Material and methods. CT scan analysis of 75 children with newly diagnosed, verified Hodgkin’s lymphoma was performed at the primary staging and after treatment. All studies were performed with contrast enhancement, scanning on a 16-slice computed tomography in the precontrast, arterial, venous and delayed phases. The radiation dose and the diagnostic value of each phase were assessed.Results. Using the reduced CT protocol for primary patients allows significantly reduce the cumulative ED by 3.8 times and by 3.6 times for dynamic scanning. Using the abbreviated protocol does not reduce the diagnostic value of CT.Conclusion. The proposed low-dose CT protocol with the reduction of contrast enhancement phases allows to obtain CT images with good diagnostic quality and reliably reduces the radiation dose to the child.